3.5.2.4.1.2 J1

Description

This function returns the first order Bessel function:

J1(x)

The formula for the equation is:


J_1(x)=\sum_{k=0}^{\infty} \frac{(-1)^{k}(x/2)^{2k+1}}{k!\Gamma(k+2)}

See the gammaln(x) function for the definition of \Gamma.

Syntax

double J1(double x)

Parameter

x

is the double at which you want to calculate the first order Bessel function.

Return

Returns the first order Bessel function at x.

Example

aa = j1(5);
aa =; //-0.32757913759147

See Also

J0, Jn, Y0, Y1, Yn,